Notes on Anomala felicia Arrow, 1910 and its relatives from Borneo with descriptions of six new species (Coleoptera: Scarabaeidae: Rutelinae). - Zorn, Carsten (Beiträge zur Entomologie = Contributions to Entomology, 2007)
Das Typenmaterial von Anomala felicia Arrow, 1910, Anomala kinabalensis Ohaus, 1916 und Anomala sarawakensis Ohaus, 1916 wird revidiert. Für die nominellen Taxa Anomala felicia Arrow, 1910 und Anomala ovatula kinabalensis Ohaus, 1910 werden Lectotypen designiert. Anomala snizeki sp. n., Anomala kaltengensis sp. n., Anomala bifida sp. n., Anomala aequalis sp. n., Anomala mahakamensis sp. n. und Anomala manseri sp. n. werden als neue Arten beschrieben.StichwörterColeoptera, Scarabaeidae, Rutelinae, Anomala, taxonomy, new species, Oriental region, Borneo.Nomenklatorische Handlungenaequalis Zorn, 2007 (Anomala), spec. n.bifida Zorn, 2007 (Anomala), spec. n.felicia Arrow, 1910 (Anomala), Lectotypekaltengensis Zorn, 2007 (Anomala), spec. n.kinabalensis Ohaus, 1910 (Anomala), Lectotype described as Anomala ovatula kinabalensismahakamensis Zorn, 2007 (Anomala), spec. n.manseri Zorn, 2007 (Anomala), spec. n.snizeki Zorn, 2007 (Anomala), spec. n.